P06.11 Immunotargeting of CD98hc for elimination of radioresistant head and neck squamous cell carcinoma. (1st October 2020) - Köseer, AS; Arndt, C; Feldmann, A; Linge, A; Krause, M; Dubrovska, A; Bachmann, M
Abstract : Background: Most patients with head and neck squamous cell carcinomas (HNSCC) are diagnosed during a locally advanced stage and may show therapy resistance. Retrospectively, we showed that low CD98hc mRNA and protein levels are significantly associated with better locoregional tumor control in HNSCC patients. 1, 2 Inhibition of CD98hc expression decreased tumor radioresistance suggesting that CD98hc could be a target for HNSCC radiosensitization. One of the strategies for radiosensitization is targeted immunotherapy. However, Chimeric Antigen Receptor (CAR)-equipped T-cell therapy cannot be fully controlled. Therefore, we developed a switchable UniCAR system that is in phase I clinical trial (NCT04230265 ) [3]. UniCAR T cell activity and specificity are controlled by the presence of target modules (TM) with short half-lives. 3 We aim to define the clinical value of treatment approaches by combining radio(chemo)therapy with CD98hc-targeted immunotherapy. Materials and Methods: We have used previously described radioresistant Cal33 HNSCC cells. 2 These tumor cells were cocultured with UniCAR T cells in the presence or absence of a novel CD98 TM. Specific cell lysis in both in vitro 2D and 3D cultures and tumor cell targeting in the experimental mice was assessed. 4 Results: Our data shows that CD98-redirected UniCAR T cells can induce cell lysis of radioresistant HNSCC cells in vitro and in vivo models. The combination of the UniCAR system with radio(chemo)therapy can be potentially used for the improvement of the treatment efficacy in patients with metastatic radioresistant tumors. The most promising combination of therapeutic approaches will be further tested in xenograft tumor models to evaluate the best performing combination of immunotherapy and radio(chemo)therapy. Conclusions: Overall, it was shown that tumor cells with radioresistant properties can be eradicated via the UniCAR system by targeting CD98hc in an antigen-specific manner. References: Linge A, et al ., Low Cancer Stem Cell Marker Expression and Low Hypoxia Identify Good Prognosis Subgroups in HPV(-) HNSCC after Postoperative Radiochemotherapy: A Multicenter Study of the DKTK-ROG. Clin Cancer Res 2016. 22 (11): 2639–49. Digomann D, et al ., The CD98 Heavy Chain Is a Marker and Regulator of Head and Neck Squamous Cell Carcinoma Radiosensitivity. Clin Cancer Res 2019. 25 (10): 3152–63. Bachmann M, et al ., The UniCAR system: A modular CAR T cell approach to improve the safety of CAR T cells. Immunol Lett 2019;211 :13–22. Arndt C, et al ., UniCAR T Cell Immunotherapy Enables Efficient Elimination of Radioresistant Cancer Cells. Oncoimmunology 2020.9 (1): 1743036. Disclosure Information: A.S. Köseer: None. C. Arndt: None. A. Feldmann: None. A. Linge: None. M. Krause: None. A. Dubrovska: None. M. Bachmann: E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; GEMoaB.